2020
DOI: 10.3389/fnhum.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

Music Form but Not Music Experience Modulates Motor Cortical Activity in Response to Novel Music

Abstract: External cues, such as music, improve movement performance in persons with Parkinson's disease. However, research examining the motor cortical mechanisms by which this occurs is lacking. Research using electroencephalography in healthy young adults has revealed that moving to music can modulate motor cortical activity. Moreover, motor cortical activity is further influenced by music experience. It remains unknown whether these effects extend to corticomotor excitability. Therefore, the primary aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For those comparisons, significant differences occurred in electrodes FC3 (140 BPM), Cz (140 BPM), C4 (70 BPM),and T7 (70 BPM). Previous research has suggested that music style may impact sensorimotor activity (Janata et al., 2012 ; Witek et al., 2014 ; Stegemöller et al., 2018b ; Izbicki & Stegemöller, 2020 ). Faster tempo, moderate syncopation, and repetitive rhythm elicit a greater urge to move while slower tempo, excessive syncopation, and non‐repetitive rhythm elicit little to no urge to move (Janata et al., 2012 ; Witek et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…For those comparisons, significant differences occurred in electrodes FC3 (140 BPM), Cz (140 BPM), C4 (70 BPM),and T7 (70 BPM). Previous research has suggested that music style may impact sensorimotor activity (Janata et al., 2012 ; Witek et al., 2014 ; Stegemöller et al., 2018b ; Izbicki & Stegemöller, 2020 ). Faster tempo, moderate syncopation, and repetitive rhythm elicit a greater urge to move while slower tempo, excessive syncopation, and non‐repetitive rhythm elicit little to no urge to move (Janata et al., 2012 ; Witek et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The raw data for each participant in the background EMG activity and each condition (i.e., single-pulse and SICI) was naturally log transformed to obtain a normal distribution. The primary outcome measure of MEP amplitude was obtained by averaging the natural log-transformed 10 MEP trials for each condition (i.e., single-pulse and SICI) (Nielsen, 1996;Clark et al, 2004;Izbicki et al, 2020). SICI was also expressed as a percentage using the formula: inhibition percentage (%) = 100 -[rest SICI MEP (conditioned pulse)/rest SP MEP (non-conditioned pulse) × 100] ( Byblow and Stinear, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The music was specifically composed for previous studies in order to control for previous experience or familiarization with the music (Izbicki & Stegemöller, 2020;Stegemöller et al, 2018Stegemöller et al, , 2021. These studies have shown that the preference for this piece (based on a 10-point Likert scale, 1 = not preferred, 5 = neutral, 10 = preferred) was 5.05 + 2.10 (Stegemöller et al, 2018) and 5.95 + 1.32 (Izbicki & Stegemöller, 2020), suggesting a neutral preference for this music condition. No participants from the previous studies were involved in this study.…”
Section: Musicmentioning
confidence: 99%